Advancements in energetic metal-organic frameworks, alkali and alkaline earth metal salts, and transition metal complexes: Predictive models for detonation velocity, heat, and pressure - Mohammad Hossein Keshavarz; Nasser Hassanzadeh; Mohammad Jafari (Defence Technology, 2025)
Recent advancements have led to the synthesis of various new metal-containing explosives, particularly energetic metal-organic frameworks (EMOFs), which feature high-energy ligands within well-ordered crystalline structures. These explosives exhibit significant advantages over traditional compounds, including higher density, greater heats of detonation, improved mechanical hardness, and excellent thermal stability. To effectively evaluate their detonation performance, it is crucial to have a reliable method for predicting detonation heat, velocity, and pressure. This study leverages experimental data and outputs from the leading commercial computer code to identify suitable decomposition pathways for different metal oxides, facilitating straightforward calculations for the detonation performance of alkali metal salts, and metal coordination compounds, along with EMOFs. The new model enhances predictive reliability for detonation velocities, aligning more closely with experimental results, as evidenced by a root mean square error (RMSE) of 0.68 km/s compared to 1.12 km/s for existing methods. Furthermore, it accommodates a broader range of compounds, including those containing Sr, Cd, and Ag, and provides predictions for EMOFs that are more consistent with computer code outputs than previous predictive models.